Perencanaan dan Pembuatan Aplikasi Pengerjaan Ujian Nasional Tingkat SMP Berbasis Android - M. Diarmansyah Batubara; Evta Indra (Program Studi Sistem Informasi, 2018)
This study attempts to apply based program as a means of interactive mobile link between students with the national examination, at the school. The implementation of national exam junior high school in Medan especially the National Examination Based a Computer (NEBC) are still in a bad condition, because the implementation of infrastructure NEBC facilities have not been accepted, the facts just a few schools that had facilities able to NEBC participates and most schools use the National Exam Paper Pencils (NEPP). Information technology very important as the expansion of learning opportunities and the community information in Indonesia. This research uses mobile technology is an information and communication technology that can be used in the world of Indonesian education. Based on the observations, the solution offered is planning and making an Android-based junior high school national exam application.Keywords: National Examination Based a Computer, Mobile, Android